Stressful life events, resources and access: key considerations in quitting smoking at an Aboriginal Medical Service - DiGiacomo, Michelle; Davidson, Patricia; Davison, J.; Moore, L.; Abbott, P. (Blackwell Publishing, 2007)
Objective: Aboriginal and Torres Strait Islander people experience adverse health outcomes and have high rates of smoking and related illnesses. This brief report describes stress as a barrier to quitting smoking derived from reflections within an Aboriginal Medical Service and makes recommendations for intervention development. Methods: A high-intensity smoking cessation program was conducted within a suburban Aboriginal Medical Service in Western Sydney, Australia, over a 10-month period. The intervention included weekly cessation counselling sessions and dispensation of free nicotine replacement therapy (NRT). Results: During the observation period, 32 clients made quit attempts. To date, three clients (9%) have quit smoking. Chronic and intercurrent life stressors were noted to be the main barriers to smoking cessation described by participants. Conclusions: Achieving smoking cessation among Indigenous people is made significantly more complex because of multiple life stressors experienced. Implications: Future interventions targeting Indigenous Australians should take greater account of stressful life events and their impact on quitting smoking.